Cytokines and dysregulation of the immune response in human malaria - Alves, Maria de Fátima Costa (1992)
ABSTRACT: The dysregulation of the immune response by malaria parasite has been considered as a possible constraint to the effectiveness of malaria vaccination. In spite of the important role interleukin-I (IL-1) in malaria are lacking. We found that only 2 out of 35 subjectswith acute malaria showed increased levels of serum IL-1 α by enzyme immunoassay. To assess whether IL-1 could interfere with T- lymphocyte responses, blood mononuclear cells from patients infected with Plasmodium falciparum, P. vivax, or healthy subjects were cultured with phytohemagglutinin, and lymphocyte proliferation measured 72h later by 3H-thymidine incorporation. Our data showed that T-lymphocyte responses are depressed both in P. falciparum (10,500 ñ 2,900) and P. vivax malaria (13,000 ñ 3,300), as compared to that of healthy individuals (27,000 ñ 3,000). Addition of IL-1 partially reserved depression of malaria lymphocytes, but had no effect on normal cells. On the other hand, T-lymphocytes from malaria infected-subjects presented a minimal decrease in proliferation, when cultured in the presence of exogenous PGE2. These data indicate the occurrence of two defects of immunoregulation in malaria: a deficiency of IL-1 production by monocytes/macrophages, and an increased resistance of lymphocytes to the antiproliferative effect of PGE2.